2021
DOI: 10.1007/s10067-021-05940-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and protective associations of the lupus low disease activity state in a prospective Chinese cohort

Abstract: Objective To investigate the frequency and determinants of achieving the lupus low disease activity state (LLDAS), and the effect of LLDAS attainment on disease flare and damage accrual in a prospective, single-center cohort of Chinese lupus patients. Methods Baseline and follow-up data from consecutive patients at the Peking University First Hospital were collected from January 2017 to June 2020. Results A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In the multivariate model of the same study, African American ethnicity, hypocomplementemia, serositis, kidney involvement, arthritis, anti-RNP, anti-dsDNA, vasculitis, malar rash, discoid rash, thrombocytopenia, and immunosuppressive use were found as negative predictors of LLDAS-50. Older age at the time of diagnosis, longer disease durations, higher education levels, and higher hydroxychloroquine intake rates were positive predictors of LLDAS-50 (17,18,19). Likewise, it has been shown that LLDAS is an achievable goal in clinical practice, but the achievement of LLDAS is more difficult among patients with discoid rashes, high anti-dsDNA levels, and hypocomplementemia (19).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the multivariate model of the same study, African American ethnicity, hypocomplementemia, serositis, kidney involvement, arthritis, anti-RNP, anti-dsDNA, vasculitis, malar rash, discoid rash, thrombocytopenia, and immunosuppressive use were found as negative predictors of LLDAS-50. Older age at the time of diagnosis, longer disease durations, higher education levels, and higher hydroxychloroquine intake rates were positive predictors of LLDAS-50 (17,18,19). Likewise, it has been shown that LLDAS is an achievable goal in clinical practice, but the achievement of LLDAS is more difficult among patients with discoid rashes, high anti-dsDNA levels, and hypocomplementemia (19).…”
Section: Discussionmentioning
confidence: 94%
“…Older age at the time of diagnosis, longer disease durations, higher education levels, and higher hydroxychloroquine intake rates were positive predictors of LLDAS-50 (17,18,19). Likewise, it has been shown that LLDAS is an achievable goal in clinical practice, but the achievement of LLDAS is more difficult among patients with discoid rashes, high anti-dsDNA levels, and hypocomplementemia (19). SLEDAI scores higher than 10 have…”
Section: Discussionmentioning
confidence: 95%
“…There were varying degrees of maintaining LLDAS: 29 (15.7%) patients were in LLDAS for 100% of observations, 53 (28.7%) for 50 to 100% of observations, and 58 (31.4%) in LLDAS for < 50% of observations. 21 Lastly, in a longitudinal collaborative study in nine countries in the Asia-Pacific region, 1846 patients were assessed and the criteria for LLDAS were met by 44%. There was low likelihood of LLDAS in patients with shorter disease duration (OR 0.31, 95 % CI 0.19-0.49), history of discoid rash (OR 0.66, 95 % CI 0.49-0.89), renal disease (OR 0.60, 95 % CI 0.48-0.75), elevated double stranded DNA (OR 0.65, 95 % CI 0.53-0.81) or low complement (OR 0.52, 95 % CI 0.40-0.67).…”
Section: Discussionmentioning
confidence: 99%
“…They found increasing proportion with organ damage within two years (37/104 or 35.6%) and three years (11/21, 52.4%). 21 A prospective study of a multiracial group of 350 patients in the UK since 1991 showed an incidence of damage accrual at two years postdiagnosis of 39.6/1000 patient-years, and incidence of serious organ damage (SDI score ≥3) of 10.4/1000 patient-years. 24 Furthermore, being able to maintain LLDAS was similarly associated with less organ damage accrual in a cohort of 293 Caucasians observed over seven years.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of remission in SLE and LLDAS remission have been compared in the field of reducing flares and damage progression in various studies [ 29 , 30 ]. Based on these data, attempts were made to reach a definite conclusion that deeper and longer remission is associated with stronger protective effects against organ damage and its consequences.…”
Section: Prevalence Predictors and Prognostic Benefits Of Remissionmentioning
confidence: 99%